Plan of psychological actions for anger control in taekwondo athletes - Abalos, Carelia Serrano; Corcho, Osvaldo Jiménez Pérez de (International research journal of management, IT and social sciences, 2020)
The present investigation has carried out intending to design a plan of psychological actions that contributes to the control of anger in athletes of the Taekwondo school category of the EIDE «Captain Orestes Acosta» of Santiago de Cuba. For this, a diagnosis of the state of anger and its expression has made to ten athletes of that category, with the application of observations, interviews and the expression inventory of Ira Trago-Estado, child-adolescent version. The experience of anger has described, describing the situations and related thoughts, where the efforts and/or resources of the athletes are not sufficient, effective or adequate for their control. This diagnosis made possible the elaboration of the plan with actions designed for the evaluation and adequate response to the situations that have propitiated in the course of the preparation and the competences.